THE CONSTRUCTION OF AGENDA SETTING IN THE DA’WAH BROADCASTING OF SALAM TV - Farid, Ahmad Salman; Manda, Vijaya Kittu (al-Balagh : Jurnal Dakwah dan Komunikasi, 2025)
Islamic media platforms such as Salam TV have reshaped religious broadcasting, influencing both public discourse and spiritual identity. However, research has largely emphasized audience impact, with little attention given to how editorial and institutional processes shape da’wah content, particularly in campus-based platforms. This study adopts a qualitative case study approach to explore agenda-setting within Salam TV’s da’wah programming. Data were collected through in-depth interviews, document analysis, and focus group discussions involving 140 informants, including broadcasting managers, content producers, Islamic scholars, and viewers. Thematic analysis was employed to identify recurring patterns in editorial decision-making and institutional influence. Findings reveal that Salam TV’s editorial priorities are strongly shaped by theological imperatives rooted in the Salafi tradition. Programming themes consistently emphasize ‘aqīdah, akhlāq, and Islamic jurisprudence, supported by structured mechanisms for selecting themes, developing scripts, and conducting theological reviews. While audiences value the program’s theological precision, younger viewers tend to prefer more inclusive language and contemporary framing. The study highlights the tension between theological rigor and communicative adaptability in campus-based Islamic media. To remain relevant and credible across diverse audiences, Islamic broadcasters must integrate theological accuracy with responsive communication strategies.